Cost and Effectiveness of Screening Methods for Type 2 Diabetes - Srichang, Nipa; Jiamjarasrangsi, Wiroj; Aekplakorn, Wichai; Supakankunti, Siripen (Journal of Health Science of Thailand, 2017)
The aims of this study were to compare the performance, cost, and cost per case identified of four screening methods in identifying individuals with type 2 diabetes. This study was conducted among people aged 35 - 60 years with no known type 2 diabetes (2,977 people). All subjects completed a set of screening questionnaires and followed by fasting plasma glucose (FPG) testing for those with positive questionnaire screening result. Universal FPG testing was conducted and used as the reference for all other screening methods to compare with. One-time screening performance and costs were analyzed from both provider and societal perspectives. The results show that sensitivities of all screening methods for men and women were high to very high (92-100% and 44- 94% respectively), while the specificities were low to moderate (21-48% and 32-58% respectively). The total cost of method 3 and method 2 which the most effective screening for type 2 diabetes of men and women were 196,157 and 202,275 baht per 1,000 persons screened. Their corresponding cost per case identified were 12,260 to 14,516 (men) and 23,526 to 45,244 baht (women) from societal perspective, and 5,816 to 7,200 and 11,048 to 21,003 baht per newly detected case from a provider perspective. Thus, screening method 3 which proposed by Aekplakorn et al was the most effective and follow by method 2 which proposed by MOPH.